Zinc Oxide Nanoparticles (ZnONPs) Supplementation in Semen Extender Improves Post-Thaw Quality and Antioxidant Capacity of Gir Bull Spermatozoa - Ram, Dilip R; Parikh, Suryakant S; Panodara, Ramesh J; Chaudhary, Jignesh K; Vala, Karsan B; Solanki, Jayesh Z; Vadher, Dhruv V (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A study was conducted on the semen of four Gir bulls over a six-month period to evaluate the impact of different concentrations of Zinc  Oxide Nanoparticles incorporated into the Andromed extender on sperm quality and oxidative stress parameters of cryopreserved semen.  A total of 16 semen ejaculates (4 ejaculates per bull) with initial motility more than 70% were used. Semen was extended in Andromed  extender @ 80 million sperm per mL, divided into four equal aliquots, and then 1 mg/mL stock solution of ZnONPs was appropriately  added to achieve final concentrations of 0.0, 0.5, 1.0, and 1.5 µg/mL. The diluted semen was filled into 0.5 mL French Medium straws,  sealed, equilibrated at 4°C for 4 h, and frozen in liquid nitrogen vapour using a conventional wide-mouth freezer. Thawing was done  next day in a water bath at 37°C for 30 sec, and various sperm quality parameters and oxidative markers were assessed. Results showed  that post-thaw sperm motility, viability, HOST reactive sperm, and acrosomal integrity were significantly (p
Keywords: Cryopreservation; Gir bull semen; Oxidative marker; Sperm quality parameters; Zinc Oxide Nanoparticles (ZnONPs)